The Role of Capital Structure, Profitability, and Dividend Policy on Firm Value in Indonesian Manufacturing Companies - Andika Putra; Muizzuddin; Kemas Muhammad Husni Thamrin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the effects of financial leverage (DER), profitability (ROA), and dividend policy (DPR) on firm value (Tobin’s Q) among manufacturing companies listed on the Indonesia Stock Exchange over the 2018–2024 period, grounded in Agency Theory. The sample was obtained through purposive sampling from an initial pool of 93 companies, resulting in 69 companies after the exclusion of 24 firms containing residual outliers via entity-level removal, yielding 483 observations in a balanced panel dataset. The Fixed Effect Model was employed, with bootstrapping (10,000 replications) for robust inference. Results indicate that financial leverage and profitability positively and significantly affect firm value, with profitability as the most dominant determinant, while dividend policy shows no significant effect. Simultaneously, all three variables are significant. These findings confirm the empirical relevance of Agency Theory in Indonesian manufacturing firms.